DIVUSI INOVASI DAN BUDAYA: PENGGUNAAN BATEE RANUP DALAM TRADISI MEU-UROH (STUDI KASUS DI DESA COT LAGAN KECAMATAN WOYLA KABUPATEN ACEH BARAT) - Rahma Hidayati; Reni Juliani; Nidar Nidar (SOURCE : Jurnal Ilmu Komunikasi, 2018)
Aceh is a region rich in tradition. One of the traditions that continues to be practiced is the meandering tradition. But in practice this tradition has undergone innovation. The ancient traditions were carried out by bringing a meaningful message that has a high meaning and now this tradition is carried out by bringing a "betel tree" print invitation. This happened to Cot Lagan community of Woyla Subdistrict of Aceh Barat District, so there was a cultural shift in the mega-uroh tradition. The purpose of this study is to know the cause of the cultural shift. This research uses qualitative method with data collection technique through interview and documentation. The results of the study show that the shift in cultural use of batee ranup in the tradition of meu-uroh is caused by the lack of understanding and love of the people about the culture so it is very easy to accept the new culture that enters and develops among them. This shift in culture is also due to the rapid development of technology that has brought many changes in the life of the community, including in terms of culture. The development of this technology brings betel arts to the middle of the community as an invitation and gradually replaces the batee ranup position in the meu-uroh tradition. In addition, the use of betel arts invitations is also considered as cheaper and more practical in comparison to using the batee ranup. Keywords: Innovasion, Cultural, Batee Ranup, Meu-uroh.